SYNTHETIC EDUCATIONAL CONCEPT OF ESSENTIALISM: A CRITICAL ANALYSIS FROM AN ISLAMIC EDUCATIONAL PERSPECTIVE - Cut Nyak Marlina; Warul Walidin Ak; Silahuddin (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2025)
Essentialism is a school of educational philosophy that emphasizes the importance of core values in the educational process. This school emerged as a response to progressivism, which was considered too flexible and less stable. From an Islamic perspective, essentialist education has a strong relevance because it emphasizes the inheritance of noble values, discipline, and stability in learning. Islamic education itself is based on the Qur'an and Hadith, which emphasize the importance of science as well as moral and spiritual character building. This research uses the literature review method to analyze the relationship between the concept of essentialism and Islamic education. The results show that the principles of essentialism can be applied in Islamic education by balancing religious and general sciences. The curriculum must be designed to produce students who are not only academically intelligent, but also have good morals and are able to face the challenges of the times. The role of teachers is very important in guiding students to understand knowledge deeply and apply it in life. Thus, the integration of essential education in Islamic education can produce individuals who are knowledgeable, noble, and ready to contribute to society.